Produksi Biji Bawang Merah Samosir Aksesi Simanindo Terhadap Konsentrasi GA3 dan Lama Perendaman di Dataran Tinggi Samosir - Berson Berson; Mariati Mariati; Rosita Sipayung (Universitas Sumatera Utara, 2015)
The aim of the research was to identify the effect of GA3 concentration and soaking period on the seed yield of shallot. Research was conducted at Hatoguan Village, Palipi Subdistrict, Samosir from February up to July 2014, carried out by using randomizes block design with two factors, replicated three times. The first factor was GA3 concentrations (50 ppm; 100 ppm; 150 ppm; 200 ppm; and 250 ppm) and the second was soaking period (30; 60; and 90 minutes). Parameters observed were the number of plant producing flowers per plot, the number of umbel per plot, seed weight per umbel, and seed weight per plot. The results showed that among all parameters observed, only the number of plants producing flowers per plot and seed weight per umbel were affected by GA3 concentration. The highest number of plants producing flowers and seed weight per umbel were produced by G4 (200 ppm GA3) i.e 10,780 plants (43,12 %) and 0,202 g respectively. Meanwhile, only seed weight per umbel was significantly affected by soaking period. The correlation between soaking period and seed weight per unbel showed positive linear regression.Key word: GA3 consentration, soaking period, shallot